A Letter to Peter Abotomey and Noel Macainsh - Wright, Judith (LiNQ (Literature in North Queensland), 2016)
I found your articles in the first issue of Vol 6 (1978) interesting in many ways. Perhaps I should apologise, Peter, to you and the pigeons of your Australian Literature class for having put the cat among you in so distressing a way. But no, I don't think I should. If you had read the essays in the first section of Because I was Invited ('Mainly about Poetry'), you would have been amply forewarned on my views, or most of them, on Academe vs. Poetry. As for talking about my own poetry, it is I would have thought notorious by now that I avoid this as far as humanly possible.